Control of Listeria monocytogenes in milk by using phage cocktail - Sanlibaba, Pinar (2022)
Biocontrol applications such as using phages against the contamination of Listeria monocytogenes are promising trends in terms of reducing the use of chemical additives in food industry. The aim of this study was to determine the effectiveness of Listex P100 phage (phage P100) on different Listeria monocytogenes strains (PL2, PL3, PL9 and PL10) in pasteurized milk and broth. Survival data of L. monocytogenes were successfully described by Weibull model. Time parameter of the Weibull model was used to evaluate the phage-resistances of L. monocytogenes strains. The reduction of L. monocytogenes was greater in broth than in milk regardless of the temperature level and it was significantly higher at 30 °C than at 4 °C in both media. The reductions of L. monocytogenes strains by the phage treatment were between 2.7 to 3.4 log10 units at 30 °C and 1.4 to 2.1 log10 units at 4 °C after 4 days of incubation in broth whereas 1.9 to 2.9 log10 units and 1.0 to1.6 log10 units were observed after 4 days of incubation in milk at 30 °C and 4 °C, respectively. It was found that L. monocytogenes PL2 is the most phage-resistant strain in broth at 30 °C and at 4 °C, and in milk at 30 °C, while L. monocytogenes PL9 is the most phage-resistant L. monocytogenes strain in milk at 4 °C. This study demonstrated P100 phage could be used to control L. monocytogenes counts in milk.